Adrenal Infarction - An Early and Late Complication of COVID-19: A Case Report - Gigiabdze, Mariam; Kebadze, Keti; Beriashvili, Mariam; Dvaladze, Mariam; Vardosanidze, Elene; Abuladze, Ana; Gigolashvili, Tamar; Modebadze, Melita (Indonesian Journal Publisher, 2025)
Progressive respiratory failure and the hyperinflammatory response are among the primary causes of death in COVID-19. Although various organ system complications have been identified post-COVID, among which one of the most important endocrine disorders is hypothalamus-pituitary-adrenal gland connection disruption, there is still little information about virus-induced adrenal gland tropism. Among the multisystemic effects of the COVID-19 pandemic, researchers are focusing on adrenal hemorrhages and infarcts. The aim of the article is to present and discuss clinical case of autoimmune adrenal gland failure developed post-COVID. The impact of COVID-19 was studied in 3 phases: The phase of acute active infection, Immediate post-infection phase and Long-term recovery phase. Adrenal insufficiency associated with COVID-19 has been reported in the literature in the context of hemorrhage and infarction. As a result of the studies, it was determined that the administration of large amounts of hydrocortisone to patients during the acute active phase of COVID-19 makes it impossible to fully evaluate the function of the gland. After stopping treatment with hydrocortisone, adrenal insufficiency was detected 1 month following the infarction. It has been established that during the long-term recovery phase, the possibility of insufficient cortisol is observed in most patients. In this case, the cause is central adrenal insufficiency. Considering all this, we can say that adrenal gland failure is a late phase complication of COVID-19. After transmission of COVID-19, complications are associated with insufficient production of cortisol by the adrenal gland. It is important to evaluate issues in post-COVID patients to avoid life-threatening adrenal crises.